2017
DOI: 10.1186/s13195-017-0289-z
|View full text |Cite
|
Sign up to set email alerts
|

Structured physical exercise improves neuropsychiatric symptoms in acute dementia care: a hospital-based RCT

Abstract: BackgroundThe primary objective of this trial is to investigate the effects of a short-term exercise program on neuropsychiatric signs and symptoms in acute hospital dementia care.MethodsWithin a hospital-based randomized controlled trial, the intervention group conducted a 2-week exercise program with four 20-min exercise sessions on 3 days per week. The control group conducted a social stimulation program. Effects on neuropsychiatric signs and symptoms were measured via the Alzheimer’s Disease Cooperative St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…In recent years, there has been a growing interest in physical exercise as a non-pharmacological treatment for dementia 8,9 . Certainly, some studies have reported that regular physical exercise can favorably affect the physical and cognitive functions of patients with dementia 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in physical exercise as a non-pharmacological treatment for dementia 8,9 . Certainly, some studies have reported that regular physical exercise can favorably affect the physical and cognitive functions of patients with dementia 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many geriatric syndromes may also be prevented by reducing NPs . However, there is a limited number of studies upon the effect of physical activity on NPs, of which the results are conflicting . Therefore, this review is aimed to explain the current literature and the effects of physical activity on NPs in patients with AD and to raise awareness about this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity can reduce the risk or delay the onset of AD 16 and has a positive effect on cognitive flexibility, depressive symptoms, cardiovascular health, sleep (REM sleep behavior disorder), and general wellness, which are predictors for ongoing neurodegenerative process in patients without dementia 17,18 ; it can also improve cognitive functions and NPs in patients with dementia, and the role of physical activity is a novel area of research in dementia, in particular in AD. [19][20][21][22] Furthermore, many geriatric syndromes may also be prevented by reducing NPs. 23 However, there is a limited number of studies upon the effect of physical activity on NPs, of which the results are conflicting.…”
mentioning
confidence: 99%
“…Recently Bürge et al [30] found no benefit of four weeks exercise programme over a social activity programme in ADL. Moreover Fleiner et al [31] examined two weeks exercise programme.…”
Section: Introductionmentioning
confidence: 99%